The Effect of Financial Literacy and Pocket Money on Investment Interest in Management Study Program Students for the 2022 Academic Year, Universitas Pembangunan Panca Budi - Yogi Purwanto; Noni Ardian; Hernawaty (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2026)
The development of investment in Indonesia has shown a significant increase in recent years, supported by the ease of access to information and the presence of various digital investment platforms. This condition encourages the importance of increasing investment interest among the younger generation, especially students, as a group that has great potential in building investment habits from an early age. This study aims to analyze the influence of financial literacy and pocket money on investment interest in students of the Management Study Program for the 2022 Academic Year, Panca Budi Development University. This study uses a quantitative approach with the type of associative research. The population in this study is all students of the Management Study Program of the Panca Budi Development University of Medan class of 2022 which totals 603 people. The sample was determined using the Slovin formula with an error rate of 10% so that a sample of 86 respondents was obtained. The data collection technique was carried out through the distribution of questionnaires, while the data analysis technique used multiple linear regression with the help of the SPSS version 32 program. The results showed that financial literacy had a positive and significant effect on investment interest with a t-calculated value of 2.701 greater than the t-table of 1.989 and a significance value of 0.008 < 0.05. Pocket money also has a positive and significant effect on investment interest with a t-calculated value of 8.621 greater than the t-table of 1.989 and a significance value of 0.001 < 0.05. Simultaneously, financial literacy and allowance had a significant effect on investment interest with an F-calculation value of 38.119 greater than the F-table of 3.11 and a significance value of 0.001 < 0.05. The value of the determination coefficient (R²) of 0.479 showed that financial literacy and pocket money were able to explain the variation in investment interest by 47.9%, while the remaining 52.1% was influenced by other factors not studied in this study. Thus, increasing financial literacy and good pocket money management can encourage an increase in student investment interest.